Do screening tools assess palliative care needs and 12-month mortality in patients admitted to hepatology in-patient wards?. Issue 3 (27th May 2021) - Low, Joseph; Carroll, Catherine; Wilson, Jo; Craig, Rachel; Vadera, Shree; Cococcia, Sara; Thorburn, Douglas; Stone, Patrick; Marshall, Aileen; Vickerstaff, Victoria
Abstract : Background: Many liver patients have unmet palliative care needs, but liver clinicians are unclear whom to refer to specialist palliative care (SPC). The Supportive and Palliative Care Indicator Tool (SPICT) and the Bristol Prognostic Screening Tool (BPST) could help identify suitable patients, but neither has been tested for this role. This study evaluated their role as screening tools for palliative care needs and for predicting 12-month mortality. Methods: A case note review of hepatology in-patients, who were not peritransplant and post-transplant status, was conducted in one tertiary unit. Main outcomes were clinical judgement of need for SPC referral, BPST scores, SPICT attribution of caseness and 12-month survival status. Discriminatory ability of tools was assessed using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and area under the receiver operating characteristic (AUROC) curve. Results: 117 medical notes were reviewed for survival analysis, 47 of which were additionally assessed for suitability for SPC referral, using clinical judgement. SPICT (sensitivity=93%; PPV=93%; AUROC=0.933) and BPST (sensitivity=59%, PPV=79%, AUROC=0.693) demonstrated excellent and good performance, respectively, in predicting patients' need for SPC referral. SPICT and BPST only had moderate ability at predicting death at 12 months (PPV: 54% and 56%, respectively). Conclusion: SPICT and BPST show potential as screening tools for identifying patients for referral to SPC. Further work is needed to determine how to implement these tools in a clinical setting.